Microgênese do desenvolvimento sociocultural do raciocínio lógico-matemático mediado por tecnologias educacionais - Silva Júnior, Augusto Márcio Da (2018)
It is adopted as a premise of this applied research to get indications of the development of logical-mathematical reasoning abilities by the learning in programming in blocks, mediated by the use of digital technologies of information and communication. To this end, online trainings were carried out, with people of different age groups and schooling, via virtual learning environment (AVA) Moodle, configured in order to foster interactions among participants based on sociocultural theories. In addition, the principles of computation and computational thinking focused on the Code.org and Scratch tools were introduced, consisting of an online education environment with multiple challenges divided into stages and degrees of difficulty. The results indicated that the proposal had the main expected result (improvement in logical-mathematical reasoning). In addition, there was a positive perception of improvement in the resolution of everyday problems, indicating the proposal as promising for the teaching-learning of computational thinking and block programming.